Analisis Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Pemerintah Kota Bogor Tahun 2019-2023 - Viony Monica Ratu; Stephanus Andi Adityaputra (AKUNTANSI 45, 2025)
This research aims to analyze the financial performance of the Bogor City Government through the realization of the Regional Revenue and Expenditure Budget (APBD) during the 2019-2023 period. The method used is quantitative descriptive analysis with secondary data obtained from the Bogor City Government website, namely https://ppid.kotabogor.go.id. The analysis was carried out based on the calculation of seven ratios, namely the ratio of independence, dependency, effectiveness of Original Regional Income (PAD), efficiency, income growth, income budget variance, and degree of decentralization. The research results show that the financial independence of the City of Bogor is in the medium category, with high dependence on income from outside the region. The effectiveness of PAD shows very good performance, although the efficiency of budget management still requires improvement. Revenue growth shows a positive trend, and budget variance reflects fairly good management. In addition, the degree of decentralization reflects the ability of local governments to make decisions that are responsive to community needs.